IMPROVEMENT OF RICE GROWTH AND PRODUCTIVITY THROUGH BALANCE APPLICATION OF INORGANIC FERTILIZER AND BIOFERTILIZER IN INCEPTISOL SOIL OF LOWLAND SWAMP AREA - Marlina, Neni; Gofar, Nuni; Subakti, Abdullah Halim Perdana Kusuma; Rohim, Abdull Madjid (AGRIVITA, Journal of Agricultural Science, 2014)
The objective of this study was to obtain a proper balance dose between biofertilizer and inorganic fertilizer in order to increase the growth and yield of rice in Inceptisol soil of lowland swamp origin. Biofertilizer was made by enriching straw compost with N2 interceptor bacteria, phosphate solvent bacteria and growth stimulator bacteria isolated from swamp lowland in South Sumatra. This study was conducted from November 2012 to March 2013 in a greenhouse. The design used was completely randomized design (CRD) factorial, with two treatment factors consisting of inorganic fertilizer (0,25, 50, 75 and 100% recommended dosage) and biofertilizer (0, 100, 200, 300, 400 and 500 kg.ha-1). The results showed that the best treatment in term of plant height at 8 weeks after planting (WAP), the maximum number of tillers, number of productive tillers, number of grains per panicle and weight of milled dry rice were obtained in combination of 75% inorganic fertilizer and 300 - 400 kg.ha-1biofertilizer.Keywords: biofertilizer, inorganic fertilizer, lowland rice